DIGITAL TRANSFORMATION AS A MODERATOR: EXAMINING ENVIRONMENTAL DISCLOSURE, INNOVATION CULTURE, AND TAX AVOIDANCE IN INDONESIA - Risa, Nurma; Murwaningsari, Etty; Mayangsari, Sekar; Mahfar, Rosmawati (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2026)
This study develops a robust measure of corporate tax avoidance by decomposing the book-tax difference (BTD) into permanent and temporary components. Furthermore, it examines the moderating role pf digital transformation in the relationship between environmental disclosure, innovation culture and tax avoidance. The study employs Moderated Regression Analysis (MRA) to test the hypothesis. The sample comprises 620 observations from 310 company listed on The Indonesia Stock Exchange (IDX) for 2023-2024 period, excluding the financial and service company. The results indicates that the proposed corporate tax avoidance measure is robust compared to extant measurements. The study finds that environmental disclosure has a significant negative effect on tax avoidance, whereas innovation culture exhibits no significant influence. Furthermore, digital transformation strengthens the negative impact of environmental disclosure on tax avoidance; however, it does not moderate the non-significant relationship between innovation culture and tax avoidance. This finding suggests that integrating digital transformation with transparent environmental disclosure can serve as an effective corporate governance mechanism to mitigate tax avoidance.